2019
DOI: 10.1093/milmed/usy379
|View full text |Cite
|
Sign up to set email alerts
|

3D Tibia Reconstruction Using 2D Computed Tomography Images

Abstract: OBJECTIVE Skeletal stress fracture of the lower limbs remains a significant problem for the military. The objective of this study was to develop a subject-specific 3D reconstruction of the tibia using only a few CT images for the prediction of peak stresses and locations. METHODS Full bilateral tibial CT scans were recorded for 63 healthy college male participants. A 3D finite element (FE) model of the tibia for each subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this study, we demonstrated the accurate visualization of fractured regions using deep learning and 3D reconstructed images for the fractured bone from CT images. In other words, the purpose of this study was to evaluate the performance of the YOLO v4-based fracture detection method, and to show the possibility of an intuitive diagnosis by combining 3D image reconstruction and fracture detection [ 32 ]. The possibility of finding the fractured region from the 2D/3D CT images can be decreased according to internal or external conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated the accurate visualization of fractured regions using deep learning and 3D reconstructed images for the fractured bone from CT images. In other words, the purpose of this study was to evaluate the performance of the YOLO v4-based fracture detection method, and to show the possibility of an intuitive diagnosis by combining 3D image reconstruction and fracture detection [ 32 ]. The possibility of finding the fractured region from the 2D/3D CT images can be decreased according to internal or external conditions.…”
Section: Discussionmentioning
confidence: 99%